Seroprevalence of Orf virus infection among small ruminants in UPM's Foster Farms based on IgG antibody detection - Lim, Cheng Yi (2017)
Contagious ecthyma is an infectious disease caused by Orf virus; characterized by scabby lesions at the nostrils and mouth regions. It results in huge economic losses due to stunted growth or slaughter of the affected animals. There is inadequate information on the status of long-term Orf infection among small ruminants in Malaysia. This study aimed to detect the IgG antibodies against Orf virus infection in goats and sheep of selected UPM’s Foster Farms. Associated risk factors of Orf infection were also assessed. Serum samples of 90 sheep and 90 goats, together with relevant historical information were obtained from 5 randomly selected farms. Serum samples were stored at -20˚C and subjected for qualitative Enzyme-Linked Immunosorbent Assay (ELISA) test. It was found that 12.22% sheep and 14.44% goat population were already infected by Orf. In sheep, statistical analysis indicated there was a significant difference (p<0.05) in prevalence rate among genders, ages and farms. The prevalence rate in males was higher than in females. Young animals showed higher prevalence than in adults. Poorly managed farm was the highest compared to other farms. In conclusion, Orf infection is present in sheep and goats from UPM’s Foster Farms with prevalence rate in goats higher than in sheep.